2012
DOI: 10.1152/ajpendo.00587.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary emu oil supplementation suppresses 5-fluorouracil chemotherapy-induced inflammation, osteoclast formation, and bone loss

Abstract: Raghu Nadhanan R, Abimosleh SM, Su YW, Scherer MA, Howarth GS, Xian CJ. Dietary emu oil supplementation suppresses 5-fluorouracil chemotherapy-induced inflammation, osteoclast formation, and bone loss. Am J Physiol Endocrinol Metab 302: E1440 -E1449, 2012. First published March 20, 2012; doi:10.1152/ajpendo.00587.2011Cancer chemotherapy can cause osteopenia or osteoporosis, and yet the underlying mechanisms remain unclear, and currently, no preventative treatments are available. This study investigated damagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…Consistent with our histological findings, ex vivo osteoclast formation potential from the bone marrow cells of CEF-treated rats was significantly increased when compared to marrow cells of control rats. In support of our findings, the increased osteoclast formation potential and their density on trabecular bone surfaces, as well as a reduction in bone volume, have been reported previously in other chemotherapy models [11,12,20]. Moreover, the current study revealed a significant increase in the size of osteoclasts formed ex vivo from bone marrow cells of CEF-treated rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our histological findings, ex vivo osteoclast formation potential from the bone marrow cells of CEF-treated rats was significantly increased when compared to marrow cells of control rats. In support of our findings, the increased osteoclast formation potential and their density on trabecular bone surfaces, as well as a reduction in bone volume, have been reported previously in other chemotherapy models [11,12,20]. Moreover, the current study revealed a significant increase in the size of osteoclasts formed ex vivo from bone marrow cells of CEF-treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…While some previous studies have described CEFrelated adverse effects being mainly related to haematological and cardiac toxicity [27][28][29], no studies to date have reported the potential adverse effects of CEF treatment on bone health, although potential direct and indirect bone effects of these drugs individually have been reported previously. For example, a single high-dose injection of 5-FU in young rats was shown to induce severe trabecular bone loss due to enhanced resorption [12]. 5-FU was also shown to cause significant suppression of haematopoietic cell proliferation and impairment of marrow recovery after irradiation [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has indicated the involvement of oxidative stress in the pathogenesis of 5-FU-induced renal injury via excessive release of free radicals and ROS [1, 3]. The current findings revealed that 5-FU instigated lipid peroxidation and associated damage to the cellular membranes in addition to depletion of cellular GSH, SOD, GPx and TAC antioxidants; findings that coincide with previous reports [1, 42, 43].…”
Section: Discussionsupporting
confidence: 90%
“…Evidence has indicated that oxidative stress plays a central role in mediating the 5-FU-induced renal injury [1, 3]. The generation of reactive oxygen species (ROS) incurs membrane lipid peroxidation and oxidative cellular damage.…”
Section: Introductionmentioning
confidence: 99%